Are they high on steroids? Tailored interventions help improve screening for steroid-induced hyperglycaemia in hospitalised patients. Issue 1 (14th March 2018) - Kempegowda, Punith; Livesey, Alana C; McFarlane-Majeed, Laura; Chandan, Joht Singh; Smyth, Theresa; Stewart, Martha; Blackwood, Karen; McMahon, Michelle; Melapatte, Anitha Vijayan; Salahuddin, Sofia; Webber, Jonathan; Ghosh, Sandip
Abstract : Steroid-induced hyperglycaemia (SIH) is a common adverse effect in patients both with and without diabetes. This project aimed to improve the screening and diagnosis of SIH by improving the knowledge of healthcare professionals who contribute to the management of SIH in hospitalised patients. Monitoring and diagnosis of SIH were measured in areas of high steroid use in our hospital from May 2016 to January 2017. Several interventions were implemented to improve knowledge and screening for SIH including a staff education programme for nurses, healthcare assistants and doctors. The Trust guidelines for SIH management were updated based on feedback from staff. The changes to the guideline included shortening the document from 14 to 4 pages, incorporating a flowchart summarising the management of SIH and publishing the guideline on the Trust intranet. A questionnaire based on the recommendations of the Joint British Diabetes Societies for SIH was used to assess the change in knowledge pre-intervention and post-intervention. Results showed an increase in junior doctors' knowledge of this topic. Although there was an initial improvement in screening for SIH, this returned to near baseline by the end of the study. This study highlights that screening for SIH can be improved by increasing the knowledge of healthcare staff. However, there is a need for ongoing interventions to sustain this change.